(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background: Definition - A fistula-in-ano or Anal fistula is a chronic abnormal communication, usually lined by granulation tissue, which runs outwards from anorectal lumen (internal opening) to external opening on the skin of perineum or buttock (or rarely, in women, to the vagina). Fistula in ano most commonly follows an anorectal sepsis[1]. The basic principles of management of anal fistula are closure of internal opening of fistula tract, drainage of infection or necrotic tissue, and eradication of fistulous tract with preservation of sphincter function. The objectives were to compare the various aspects like per operative complications, post-operative complications, mean hospital stay in the treatment of fistula in ano using various modalities like fistulotomy, fistulectomy, setons and lift procedure. Methods:This is a randomised, comparative, prospective study of 40 cases of fistula in ano, presenting at surgical opd of V.S.Hospital, Ahmedabad attached to NHL Medical College. Out of which, 10 cases are treated by fistulectomy, 10 by seton, 10 by fistulotomy and the rest 10 cases by LIFT procedure by random selection method, during period of NOVEMBER 1, 2017 to 31st October 2018. Results:Most common age of presentation is 31-40 years and more common in males then females (M:F= 2.3:1 ). Per operative complications include bleeding seen more in patients undergoing fistulectomy. Per operative course of LIFT procedure patients was complication free. Postoperative pain seen more in patients undergoing setons procedure. Conclusions:we conclude that LIFT procedure and Fistulotomy were acceptable procedures for simple, uncomplicated low lying and high lying fistula.